2008
DOI: 10.1212/01.wnl.0000319694.14251.95
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and structural brain damage in benign multiple sclerosis

Abstract: In benign multiple sclerosis (BMS), cognitive dysfunction is associated with severe structural brain damage, which resembles that of patients with a much more disabling disease course. A reliable definition of BMS should, therefore, include the preservation of cognitive functioning as an additional requisite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 36 publications
10
72
1
5
Order By: Relevance
“…As shown by careful testing in other studies, cognitive impairment may be disabling even if the EDSS score is in the traditionally "benign" category. 12 Just as changes in physical disability may prompt a change in DMT, a decline in neuropsychological function may warrant a change in treatment in order to limit progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by careful testing in other studies, cognitive impairment may be disabling even if the EDSS score is in the traditionally "benign" category. 12 Just as changes in physical disability may prompt a change in DMT, a decline in neuropsychological function may warrant a change in treatment in order to limit progression.…”
Section: Resultsmentioning
confidence: 99%
“…Even in so-called benign MS, difficulty in the ability to process information may be great enough to prevent employment. 12 Neuropsychological deficits may be independent of physical disability. 6 Early cognitive impairment, however, may be associated with rapidly progressing physical disability as measured by the EDSS.…”
Section: Methodsmentioning
confidence: 99%
“…34 It has also been shown that patients with benign MS with cognitive impairment did not significantly differ from patients with SPMS with respect to normalized brain volume, global WML load, or GM mean diffusivity. 35 In contrast, benign patients without cognitive impairment demonstrated significant differences. Possible limitations of this study include sample size.…”
Section: Discussionmentioning
confidence: 97%
“…DT MRI quantities from the NAWM and GM were similar between patients with BMS and cognitive impairment and those with SPMS. 29 Another DT MRI study 30 showed that corpus callosum (CC) damage, in terms of both focal lesions and diffuse injury, was more pronounced in 31,32 have found correlations between impaired attention, working memory, and speed of information processing and decreased FA in the CC and other tracts mainly connecting prefrontal cortical regions. Tract abnormalities overlapped only in part with lesion location highlighting the importance of lesion-independent NAWM abnormalities in cognition.…”
Section: Damage To the Normal-appearing Wm And "Diffuse" Injury To Gmmentioning
confidence: 99%